Numerical Simulation Analysis and Research on Drag Reduction and Stability Enhancement Effect of Head Swing Based on Biomimetic Flexible Variants - Debo Qi; Yang Li; Baisheng Yang; Zhengyang Wu; Bo Li; Shichao Niu (Journal of Marine Science and Engineering)
With the intensification of the oil crisis, research on drag reduction technologies has gained increasing momentum. In tidal environments, the drag reduction effectiveness of conventional methods, such as bionic non-smooth surfaces, super-hydrophobic surfaces, biomimetic jet flow, wall surface vibration, etc., will be severely diminished. To enhance the adaptability of vehicles in variable fluid environments, this study explores the feasibility of adjusting the drag of a vehicle through active head swing variants. The flexible oscillation of the head of the vehicle was achieved by combining dynamic mesh technology with User-Defined Functions (UDFs). The oscillation process was numerically simulated using Fluent software. The results show that, when the vehicle maintains a stationary posture, biasing the vehicle’s head towards the incoming flow direction can effectively reduce the radial drag and drag moment, thereby improving the stability of the vehicle. Conversely, both the radial drag and the drag moment significantly increase. This condition can be utilized for the auxiliary turning of the vehicle. When the vehicle undergoes continuous periodic oscillation of its head, the drag characteristics are optimal with the sine oscillation mode. By adjusting the range of the head’s oscillation angle, it can further minimize the average radial drag during the head swing process, making it possible to achieve radial drag reduction and enhance the vehicle’s stability through head oscillation. This research significantly improves the stability of the vehicle in tidal environments, making it adaptable to the highly variable underwater flow conditions.